2016
DOI: 10.1007/s00268-016-3619-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Intravenous Lidocaine for Thyroidectomy: A Prospective, Randomized, Double‐Blind, Placebo‐Controlled Trial

Abstract: Clinicaltrials.gov NCT01608360.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…Of the 17 studies, seven (Teksoz et al, Choi et al, Miu et al, Kang et al, Kesisoglou et al, Ekinci et al, and Ahiskalioglu et al) reported statistically significant decreases in VAS and NRS postoperative pain scores. 23,25,27,28,35,36,40 Teksoz et al found lower VAS scores at 30 minutes, 1 hour, and at 8 hour postoperatively ( P = .03, P = .04, P = .005, respectively). 23 Kesisoglou similarly reported significantly decreased VAS scores at 0, 3, 6, 9, 12, and 24 hours after surgery ( P < .05).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Of the 17 studies, seven (Teksoz et al, Choi et al, Miu et al, Kang et al, Kesisoglou et al, Ekinci et al, and Ahiskalioglu et al) reported statistically significant decreases in VAS and NRS postoperative pain scores. 23,25,27,28,35,36,40 Teksoz et al found lower VAS scores at 30 minutes, 1 hour, and at 8 hour postoperatively ( P = .03, P = .04, P = .005, respectively). 23 Kesisoglou similarly reported significantly decreased VAS scores at 0, 3, 6, 9, 12, and 24 hours after surgery ( P < .05).…”
Section: Resultsmentioning
confidence: 94%
“…The total amount of PCA consumption (10 mg/mL meperidine) also did not differ significantly ( P > .05). 33 In regards to rescue analgesic medications, four studies (Kang et al 28 [Fentanyl: 510.75 μg vs 422.50 μg; P < .05], Choi et al 25 [Fentanyl: 550.79 ± 46.46 μg vs 598.57 ± 55.58 μg; P < .01], Karthikeyan et al 31 [Morphine PCA: 30.70 ± 4.77 mg vs 0.85 ± 3.95 mg; P = .001], and Ekinci et al 36 [Tramadol: 72.4 ± 24.5 mg vs 91.5 ± 36.8 mg; P = .027]) reported statistically significant decreases in need for additional medication. Eight studies compared bilateral superficial cervical plexus block (BSCPB) encompassing 274 patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent meta-analysis found that the efficacy of perioperative intravenous lidocaine for postoperative pain varies between surgical procedures [8]. Indeed, opioid sparing was observed after lidocaine infusion in open abdominal [9, 10] and laparoscopic [11, 12] procedures, thyroid surgery [13], and cardiac [14], thoracic [15], and major spine [16] procedures. Moreover, data suggest a reduction of CPSP development in breast surgery [4, 17].…”
Section: Introductionmentioning
confidence: 99%